A patient with insidious onset of exertional dyspnoea. Issue 5 (28th April 2005) - Eller, P; Lechleitner, M; Gschwendtner, A; Kreczy, A; Müller, L; Kaneider, N; Patsch, J R
Abstract : The case history is presented of a 42 year old woman with pulmonary artery occlusion due to tuberculous vasculitis that masqueraded as chronic pulmonary artery embolism and led to severe life threatening haemoptysis necessitating emergency pneumonectomy. It is concluded that obliterative tuberculous endarteritis of the pulmonary arteries should be considered in the differential diagnosis of any acquired obstruction of pulmonary arteries.